Awareness and adherence to lifestyle modifications in hypertensive patients presenting to tertiary care setting - Ur Rehman, Awais; Niazi, Rauf; Rehman, Hassan Ur; Javed, Ayesha (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the level of awareness and adherence to lifestyle modifications in hypertensive patients. Method: The descriptive study was conducted from January to June 2019 at the Pakistan Institute of Medical Sciences, Islamabad, Pakistan, and comprised adult patients of either gender with hypertension history of at least 1 year. Data was collected using a structured questionnaire to evaluate the subjects’ awareness and adherence to lifestyle modifications for the control of hypertension. Data was analysed using SPSS 20. Results: Of the 294 patients, 160(54.4%) were women. The overall mean age was 53.3±12.1 years and mean body mass index was 27.1±5.9kg/m2, and mean duration of hypertension was 8.2±7.1 years. There were 122(41.5%) obese and 97(33%) overweight patients. Overall, 201(68.4%) patients had co-morbidities and 40(13.6%) were smokers. Of the total, 205(69.7%) knew the importance of exercise, but 104(35.4%) were doing it; 270(91.8%) were aware of restriction of sodium diet, but 244(83%) were adhering to it; 222(75.5%) knew the importance of dietary approaches to stop hypertension, but 185(62.9%) were adhering to it; and 247(84%) were aware that regular blood pressure measurement and follow-ups were important, but 150(51%) were adhering to it. Conclusion: The level of awareness regarding lifestyle modifications was found to be high in hypertensive patients, but the status of adherence was not up to the mark. Key Words: Awareness, Adherence, Diet, Exercise, Hypertension.